2013
DOI: 10.3791/50058
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative High-throughput Single-cell Cytotoxicity Assay For T Cells

Abstract: Cancer immunotherapy can harness the specificity of immune response to target and eliminate tumors. Adoptive cell therapy (ACT) based on the adoptive transfer of T cells genetically modified to express a chimeric antigen receptor (CAR) has shown considerable promise in clinical trials [1][2][3][4] . There are several advantages to using CAR + T cells for the treatment of cancers including the ability to target non-MHC restricted antigens and to functionalize the T cells for optimal survival, homing and persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Target cell cytolysis mediated by TIL was monitored using a Carl Zeiss Axio Observer fitted with Hamamatsu EM-CCD camera using 10 × 0.3 NA objective. Apoptotic cells became green when stained with Annexin V conjugated with Alexa 647as previously described (22). …”
Section: Methodsmentioning
confidence: 99%
“…Target cell cytolysis mediated by TIL was monitored using a Carl Zeiss Axio Observer fitted with Hamamatsu EM-CCD camera using 10 × 0.3 NA objective. Apoptotic cells became green when stained with Annexin V conjugated with Alexa 647as previously described (22). …”
Section: Methodsmentioning
confidence: 99%
“…We developed a high throughput in vitro Time-lapse Imaging Microscopy in Nanowell Grids (TIMING) platform which allows the interrogation of thousands of single-cell level interactions between T cells and tumor cells in confined nanowells. [6][7][8] Specifically, we compared the potency and kinetics of CD19-specific CD8 + T CAR + T cells (CAR8) and CD4 + CAR + T cells (CAR4) in their interactional behavior with CD19 + tumor cells. 7 At E:T of 1: 2-5, we found that both CAR8 and CAR4 cells can participate in multikilling through conjugation to multiple tumor cells, although CAR4 cells experience a significant delay in kinetics of killing the tumor cells ( Figure 1A).…”
Section: Tumor Cells In Vitromentioning
confidence: 99%
“…27 Fluorescently labeled annexin V was used to detect early apoptosis, and time-lapse microscopy using annexin V and Sytox (DNA dye) costaining confirmed that monitoring annexin V staining was sufficient to track eventual cell death (supplemental Video 1). Within nanowells containing a single NK cell and 1 to 3 targets, after 6 hours, 25% 6 8% (mean 6 standard deviation [SD]; n 5 5 donors) of NK cells induced apoptosis of DLETargets ( Figure 1I).…”
Section: Resultsmentioning
confidence: 92%
“…27 Briefly, CD33 1 EL4 (targets) and NK (effectors) cells were labeled for 5 minutes with 1 mM red PKH26 and green PKH67 (Sigma-Aldrich), respectively. The targets were subsequently incubated with 1 mg/mL mAb at 4°C for 20 minutes and were washed to remove excess mAb.…”
Section: Fabrication Of Nanowell Array and End-point Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation